The Inside-Out of End-Stage Liver Disease: Hepatocytes are the Keystone - Haep, Nils; Florentino, Rodrigo M.; Squires, James E.; Bell, Aaron; Soto-Gutierrez, Alejandro (Seminars in Liver Disease, 2021)
Chronic liver injury results in cirrhosis and end-stage liver disease (ESLD) which represents a leading cause of death worldwide, affecting people in their most productive years of life. Medical therapy can extend life, but the only definitive treatment is liver transplantation (LT). However, LT remains limited by access to quality donor organs and suboptimal long-term outcomes. The degeneration from healthy-functioning livers to cirrhosis and ESLD involves a dynamic process of hepatocyte damage, diminished hepatic function, and adaptation. However, the mechanisms responsible for deterioration of hepatocyte function and ultimately hepatic failure in man are poorly understood. We review the current understanding of cirrhosis and ESLD as a dynamic process and outline the current mechanisms associated with the development of hepatic failure from the clinical manifestations to energy adaptations, regeneration, and regulation of nuclear transcription factors. A new generation of therapeutics could target stabilization of hepatocyte differentiation and function to avoid the need for transplantation in patients with cirrhosis and ESLD.
Keywords: cirrhosis; terminal liver failure; hepatocyte reprogramming